Floristic composition, biological spectrum, and phytogeographic distribution of the Bin Dara Dir, in the western boundary of Pakistan - Manan, Fazal; Khan, Shujaul Mulk; Muhammad, Zahir; Ahmad, Zeeshan; Abdullah, Abdullah; Rahman, Amjad ur; Han, Heesup; Ariza-Montes, Antonio; Contreras-Barraza, Nicolás; Raposo, António (Frontiers in Forests and Global Change, 2022)
This study assessed the floristic composition, biological spectrum, and phytogeographical elements of the Bin Dara western boundary of Pakistan. The flora consisted of 140 plant species belonging to 47 families. The most dominant family was Poaceae (with 14 species), followed by Asteraceae (11 species). The biological spectrum showed the therophytes (71 species, 50.71%) as the dominant life form class, followed by mega-phanerophytes (27 species, 19.28%), nano-phanerophytes (15 species, 10.71%), geophytes (10 species, 7.14%), chamaephytes (9 species, 6.42%), and hemi-cryptophytes (8 species, 5.71%). Leaf size classes comprised of nanophylls (48 species, 34.28%), microphylls (32 species, 22.85%), mesophylls (22 species, 15.71%), macrophylls (17 species, 12.14%), leptophylls (12 species, 8.57), megaphylls (8 species, 5.75%), and aphyllous (1 species, 0.71%). Cosmopolitan was the most prominent form of phytogeographic elements (with 17 species, 12.14%), followed by pantropical and Euro-Siberian Mediterranean Irano-Turanian (14 species, 10%) each. The pluriregional represented (13 species, 9.28%), Holarctic and Mediterranean Irano-Turanian (10 species, 7.14%), Irano-Turanian and Western Himalayan (9 species, 6.42%) each. It is recommended that further study is needed to map the vegetation, its indicators, and rare species that face a huge threat of endangerment.